2008
DOI: 10.1016/j.trim.2008.01.001
|View full text |Cite
|
Sign up to set email alerts
|

TNFα in patients with end-stage heart failure on medical therapy or supported by a left ventricular assist device

Abstract: Background: In the heart elevated levels of TNFα can cause lethal heart failure, like Dilated Cardiomyopathy (DCM). The level of TNFα production is in part determined by promoter gene polymorphisms. We investigated whether the TNFα promoter gene polymorphism is in this way involved in the outcome of end-stage heart failure and predicts whether patients require left ventricular assist device (LVAD) support or can be kept on medical therapy (MT)while awaiting heart transplantation (HTx). As most patients in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…42 Similarly, plasma TNF-α levels were higher in heart failure patients treated with medical therapy compared with the healthy control subjects, and even higher in patients supported by PF-LVADs. 43 Unlike our study, the devices used in these previous studies were pulsatile pumps. Nevertheless, the findings of the previous studies which used pulsatile devices may be due to more advanced heart failure symptoms in device recipients, but may also raise the possibility that the device itself contributes to increased inflammation.…”
Section: Discussionmentioning
confidence: 81%
“…42 Similarly, plasma TNF-α levels were higher in heart failure patients treated with medical therapy compared with the healthy control subjects, and even higher in patients supported by PF-LVADs. 43 Unlike our study, the devices used in these previous studies were pulsatile pumps. Nevertheless, the findings of the previous studies which used pulsatile devices may be due to more advanced heart failure symptoms in device recipients, but may also raise the possibility that the device itself contributes to increased inflammation.…”
Section: Discussionmentioning
confidence: 81%
“…Consequently, a total of 1338 DCM cases and 1677 controls were subjected to our metaanalysis. [23][24][25][34][35][36][37][38][39] Of the 9 articles, 5 studied Caucasians, 3 studied Asians, and 1 studied Africans. With regard to the matching situation between case and control groups, 4 studies were at least age-matched healthy controls and 5 were healthy or unrelated individuals.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…An increase of TNF-alpha in the heart can cause lethal pump failure (27). An increased expression of TNFalpha has been observed in the failing human heart (24).…”
Section: Tumor Necrosis Factor-alpha (Tnf-alpha Tnf-a) Genementioning
confidence: 99%
“…Moreover, it has been shown that patients that received a donor heart with the TNF2 polymorphism had more severe rejection episodes during the first six months after HTx than patients that received a donor heart with TNF1 polymorphism. In HTx the donor TNF-alpha gene seem to play a more important role in severity of acute rejection than that of the patient (27).…”
Section: Tumor Necrosis Factor-alpha (Tnf-alpha Tnf-a) Genementioning
confidence: 99%